Análise do efeito da biofotomodulação na analgesia durante o trabalho de parto: ensaio clínico controlado - Traverzim, Maria Aparecida dos Santos (2019)
Pain during labor may be considered as an impediment for choosing a vaginal delivery. In an attempt to reduce pain during labor, several pharmacological and non-pharmacological methods are proposed. In the search for alternatives to pharmacological treatment for analgesia during labor wich are effective and to be used in both public and private institutions, this research has the objective of evaluating the effect of photobiomodulation with LED (Light Emitting Diode) in analgesia during labor. For this, a clinical trial was performed with 29 women divided into two groups: G1 (experimental group-LED) and G2 (Control group - hot bath). In the experimental group, the LED plate (red and infrared) was placed in the dorsal region of the patient from T10 to S4 level for 10 minutes, and the plate switched off automatically. The hot temperature controlled bath was performed for 30 minutes. To verify the effect of LED on analgesia during labor, the following variables were evaluated: (1) perception of pain; (2) fetal conditions using cardiotocography or intermittent fetal auscultation; (3) Apgar score in the first and fifth minutes after birth and (4) time of delivery. A statistically significant difference (p <0.05) in pain reduction was observed by means visual scale before and after application in G1 - LED (7.92 + - 1.78). Regarding the other variables, there was no statistically significant difference between the groups when comparing fetal conditions, Apgar score and delivery time. It is concluded that the LED can be considered an alternative, since it had as effect the reduction of the pain without changes in the other parameters during labor when comparing with the hot bath method used as protocol in the hospitals, demonstrating to be safe. It is suggested, however, the continuity in the clinical trials with larger samples and possible dosimetric adjustments to establish a photobiomodulation protocol for analgesia during childbirth.